Overnight Rostral Fluid Shifts Exacerbate Obstructive Sleep Apnea After Stroke. Issue 10 (October 2021) - Brown, Devin L.; Yadollahi, Azadeh; He, Kevin; Xu, Yuliang; Piper, Bryan; Case, Erin; Chervin, Ronald D.; Lisabeth, Lynda D.
Abstract : Background and Purpose: Overnight shifts of fluid from lower to upper compartments exacerbate obstructive sleep apnea (OSA) in some OSA populations. Given the high prevalence of OSA after stroke, decreased mobility and use of IV fluids among hospitalized patients with stroke, and improvement in OSA in the months after stroke, we hypothesized that overnight fluid shifts occur and are associated with OSA among patients with subacute ischemic stroke. Methods: Within a population-based project, we performed overnight sleep apnea tests (ApneaLink Plus) during ischemic stroke hospitalizations. Before sleep that evening, and the following morning before rising from bed, we assessed neck and calf circumference, and leg fluid volume (bioimpedance spectroscopy). The average per subject overnight change in the 3 fluid shift measurements was calculated and compared with zero. Linear regression was used to test the crude association between each of the 3 fluid shift measurements and the respiratory event index (REI). Results: Among the 292 participants, mean REI was 24 (SD=18). Within individuals, calf circumference decreased on average by 0.66 cm (SD=0.75 cm, P <0.001), leg fluid volume decreased by a mean of 135.6 mL (SD=132.8 mL, P <0.001), and neck circumference increased by 0.20 cm (SD=1.71 cm, P =0.07). In men, when the overnight change of calf circumference was negative, an interquartile range (0.8 cm) decrease in calf circumference overnight was significantly associated with a 25.1% increase in REI ( P =0.02); the association was not significant in women. The relationship between overnight change in leg fluid volume and REI was U shaped. Conclusions: This population-based, multicenter, cross-sectional study showed that in hospitalized patients with ischemic stroke, nocturnal rostral fluid shifts occurred, and 2 of the 3 measures were associated with greater OSA severity. Interventions that limit overnight fluid shifts should be tested as potential treatments for OSA among patients with subacute ischemic stroke. Abstract : Supplemental Digital Content is available in the text.